2022
DOI: 10.1007/s00521-022-07048-0
|View full text |Cite
|
Sign up to set email alerts
|

AI-based medical e-diagnosis for fast and automatic ventricular volume measurement in patients with normal pressure hydrocephalus

Abstract: Based on CT and MRI images acquired from normal pressure hydrocephalus (NPH) patients, using machine learning methods, we aim to establish a multimodal and high-performance automatic ventricle segmentation method to achieve an efficient and accurate automatic measurement of the ventricular volume. First, we extract the brain CT and MRI images of 143 definite NPH patients. Second, we manually label the ventricular volume (VV) and intracranial volume (ICV). Then, we use the machine learning method to extract fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…It could also provide both right and left ventricles in one cut (compared to two cuts in manual measurement). The following sections describe our AI model's novelty, advantages, and limitations [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…It could also provide both right and left ventricles in one cut (compared to two cuts in manual measurement). The following sections describe our AI model's novelty, advantages, and limitations [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…With this aim, we have demonstrated that a robust and fully automatic segmentation of brain parenchyma and ventricular system can be achieved by deep learning. Unlike previous publications on the topic, that have either excluded subjects with severe anomalies (e.g., Huff et al, 2019 ; Cai et al, 2020 ) or focused on a particular kind of disease (e.g., Zhou et al, 2020 , 2022 ), our developed algorithm is robust for two different kinds of anomalies (intracranial hemorrhage and tumors), despite being trained only on normal and hemorrhage data with partially incomplete annotations. In addition, the higher generalizability and robustness to anatomical changes does not come with a decrease in segmentation performance on normal anatomy, which is equally important.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple DL-based methods for segmentation of brain parenchyma and ventricles have been proposed: either for direct quantification (Huff et al, 2019 ; Zhou et al, 2020 ) or as a pre-processing step for registration purposes (Dubost et al, 2020 ; Walluscheck et al, 2023 ). In further studies, substructures of the brain parenchyma are segmented (Cai et al, 2020 ; Zopes et al, 2021 ) or a cross-modality approach for CT and MRI is proposed (Zopes et al, 2021 ; Zhou et al, 2022 ). However, these studies often focus on specific diseases such as hydrocephalus or are evaluated only on data of healthy or elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, while numerous studies have successfully demonstrated brain tissue segmentation and volumetric assessment using MR images 26,27 , these techniques have encountered challenges when attempted using CT scans with inferior soft tissue contrast. Recent research has thus explored robust automated and semi-automated segmentation(s) 28,29 and volumetric assessments of CT images using state-of-the-art image processing techniques centred on deep learning; specifically, segmentation models employing deep learning architectures, such as fully connected convolutional neural networks and 2D/3D U-Nets have been utilized [30][31][32][33] . However, most deep-learningbased studies have thus far been conducted using limited datasets and relied on manually annotated structural labels.…”
Section: Introductionmentioning
confidence: 99%